Գանձասարի 1714 թ. «Գաղտնի Ժողովի» արձանագրությունների վավերականության հարցի շուրջ - Մաղալյան, Արտակ
In 1886, in Saint-Petersburg, a book called The Secret of Karabakh was pub-lished under the authorship of Apres Beknazaryants. However, the actual author of the book was Bishop Makar Barkhudaryants. Soon after its publication, the book became a target of harsh criticism, by Raffi and Leo, for obvious factual errors and inventions. The two historians proved that The Secret of Karabakh was nothing but a fabrication. В 1886 г. в Санкт-Петербурге за авторством Апреса Бекназарянца вышел в свет труд под названием “Тайна Карабаха”, автором которого в действительности был епископ Макар Бархударянц. Вскоре с резкой критикой грубых фактических ошибок и вымыслов, отраженных в этой книге, выступили Раффи и Лео, которые со всей убедительностью доказали, что “Тайна Карабаха” не что иное, как литературная фальсификация.
Keywords: Արձանագրություններ; Անվավեր փաստաթղթեր